A comparative study between visible-light-activated and autopolymerizing sealants in relation to retention. - Gandini, M. [UNESP]; Vertuan, V. [UNESP]; Davis, J. M. [UNESP] (My University, 1991)
This investigation was conducted with the object of comparing the retention capacity of two visible-light-activated sealants (Concise-3M and Sealite-Kerr) with the more commonly used autopolymerizing sealant (Delton-Johnson & Johnson). The study included sixty-two children, thirty-five boys and twenty-seven girls, between six and eleven years of age. Two hundred twenty-nine first permanent molar occlusal surfaces were treated with sealants (118 maxillary molars and 111 mandibular molars). Sealants were applied according to the manufactures' instructions and cotton rolls were used for partial isolation. After six, twelve, eighteen and twenty-four months, the surfaces treated with the sealants were examined and evaluated. Three categories were used to evaluate each sealant. During each evaluation period the sealants were graded according to complete, partial, or failed retention. No significant difference was noted between Concise and Delton sealants for C when comparing maxillary and mandibular teeth. Significant differences were observed between Concise and Sealite in relation to C on the maxillary and mandibular arches and also between Sealite and Delton on the maxillary arch. There were no significant differences in retention between the maxillary and mandibular teeth, when the same type of sealant was used.